MBSR effects on positive psychological traits and experiential avoidance in head and neck cancer: a randomized controlled trial - Zheng Zhang; Qingqin Zhang; Ping Lu; Nurul Izzah Shari; Nik Ruzyanei Nik Jaafar; Mohd Razif Mohamad Yunus; Mohammad Farris Iman Leong Bin Abdullah (European Journal of Psychotraumatology)
Background: Data on the effects of mindfulness-based stress reduction (MBSR) positive psychological traits and experiential avoidance (EA) among cancer patients are lacking.Objective: This randomized controlled trial (RCT) aimed to: (1) compare the efficacy between MBSR and treatment-as-usual (TAU) control groups in increasing posttraumatic growth (PTG), hope, and optimism and reducing EA across time measurements (T0, T1, and T2) among head and neck cancer (HNC) patients and (2) evaluate the mediation effects of hope, optimism, and EA on the relationship between MBSR and PTG.Methods: A total of 80 HNC participants were randomized to MBSR (n = 40) and TAU (n = 40) groups with the researchers and data analyst blinded, and the group allocation of the participants was concealed. A one-hour MBSR session was conducted once a week, with 45 minutes of home assignments, for six weeks in the MBSR group. The outcomes across time measurements were compared using a mixed linear model following intention-to-treat (ITT) analysis. Mediation effects of hope, optimism, and EA on the relationship between MBSR and PTG were assessed with PROCESS.Results: MBSR significantly increased the degree of optimism from T0 to T1 (mean difference = 1.825, 95% CI = 0.907–2.743, SE = 0.381, p < .001) with a medium effect size (d = 0.563) and from T1 to T2 (mean difference = 1.650, 95% CI = 0.829–2.470, SE = 0.328, p < .001) with a medium effect size (d = 0.630). Initially, MBSR did not increase the degree of hope from T0 to T1 (p = .677), but it significantly increased hope from T1 to T2 (mean difference = 2.524, 95% CI = 1.676–3.373, SE = 0.340, p < .001) with a medium effect size (d = 0.735). Conversely, MBSR did not sustain the changes in the degree of PTG and EA beyond T1. EA partially mediated the relationship between MBSR and PTG, but not hope and optimism.Conclusion: MBSR can be recommended as part of the treatment regimen for HNC patients.Trial registration: ClinicalTrials.gov identifier: NCT04800419.